Evaluation of the antifungal effect of chlorogenic acid against strains of Candida spp. resistant to fluconazole: apoptosis induction and in silico analysis of the possible mechanisms of action. Issue 5 (16th May 2022) - Rocha da Silva, Cecília; Sá, Lívia Gurgel do Amaral Valente; dos Santos, Ermerson Vieira; Ferreira, Thais Lima; Coutinho, Tatiana do Nascimento Paiva; Moreira, Lara Elloyse Almeida; de Sousa Campos, Rosana; de Andrade, Claudia Roberta; Barbosa da Silva, Wildson Max; de Sá Carneiro, Igor; Silva, Jacilene; dos Santos, Hélcio Silva; et al.
Abstract : Introduction. Candida spp. are commensal fungal pathogens of humans, but when there is an imbalance in the microbiota, or weak host immunity, these yeasts can become pathogenic, generating high medical costs. Gap Statement. With the increase in resistance to conventional antifungals, the development of new therapeutic strategies is necessary. This study evaluated the in vitro antifungal activity of chlorogenic acid against fluconazole-resistant strains of Candida spp. Mechanism of action through flow cytometry and in silico analyses, as well as molecular docking assays with ALS3 and SAP5, important proteins in the pathogenesis of Candida albicans associated with the adhesion process and biofilm formation. Results. The chlorogenic acid showed in vitro antifungal activity against the strains tested, causing reduced cell viability, increased potential for mitochondrial depolarization and production of reactive oxygen species, DNA fragmentation and phosphatidylserine externalization, indicating an apoptotic process. Concerning the analysis through docking, the complexes formed between chlorogenic acid and the targets Thymidylate Kinase, CYP51, 1 Yeast Cytochrome BC1 Complex e Exo -B-(1, 3)- glucanase demonstrated more favourable binding energy. In addition, chlorogenic acid presented significant interactions with the ALS3 active site residues of C. albicans, important in the adhesion process and resistance to fluconazole. Regarding molecular docking with SAP5, no significant interactions were found between chlorogenic acid and the active site of the enzyme. Conclusion. We concluded that chlorogenic acid has potential use as an adjuvant in antifungal therapies, due to its anti- Candida activity and ability to interact with important drug targets.